Inverse Problem for a Curved Quantum Guide - Laure Cardoulis; Michel Cristofol (International Journal of Mathematics and Mathematical Sciences)
We consider the Dirichlet Laplacian operator −Δ on a curved quantum guide in ℝ  n(n=2,3) with an asymptotically straight reference curve. We give uniqueness results for the inverse problem associated to the reconstruction of the curvature by using either observations of spectral data or a boot-strapping method.